2019
DOI: 10.1111/nph.16248
|View full text |Cite
|
Sign up to set email alerts
|

The Myb‐like transcription factor phosphorus starvation response (PtPSR) controls conditional P acquisition and remodelling in marine microalgae

Abstract: Summary Phosphorus (P) is one of the limiting macronutrients for algal growth in marine environments. Microalgae have developed adaptation mechanisms to P limitation that involve remodelling of internal phosphate resources and accumulation of lipids. Here, we used in silico analyses to identify the P‐stress regulator PtPSR (Phaeodactylum tricornutum phosphorus starvation response) in the diatom P. tricornutum. ptpsr mutant lines were generated using gene editing and characterised by various molecular, geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…These data, although generated by different experimental designs (e.g., duration of P i starvation) or diatom species, indicated a global transcriptomic reprogramming, which should influence the protein composition of many cell compartments, accompanied by several physiological responses. In addition, a Myb-like transcription factor, P starvation response (PtPSR), which controls cellular adaptations to P i stress, has recently been identified in Phaeodactylum tricornutum (Sharma et al, 2019). The response to P i limitation correlates with a specific transcriptional upregulation of genes coding for alkaline phosphatases that are necessary for phosphate acquisition from DOP.…”
Section: Introductionmentioning
confidence: 99%
“…These data, although generated by different experimental designs (e.g., duration of P i starvation) or diatom species, indicated a global transcriptomic reprogramming, which should influence the protein composition of many cell compartments, accompanied by several physiological responses. In addition, a Myb-like transcription factor, P starvation response (PtPSR), which controls cellular adaptations to P i stress, has recently been identified in Phaeodactylum tricornutum (Sharma et al, 2019). The response to P i limitation correlates with a specific transcriptional upregulation of genes coding for alkaline phosphatases that are necessary for phosphate acquisition from DOP.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did find four Ca 2+ sensor-kinase genes upregulated during phosphorus limitation. Notably, they also contain recognition motifs for the phosphorus-stress Myb-like transcriptional regulator PtPSR (Sharma et al, 2019). Our work thus paves the way to future advances in our understanding of the genetic components, evolutionary distribution, and broader roles of phosphate-Ca 2+ signalling in controlling phosphorus-stress recovery in diatoms, and potentially eukaryotes more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms, and other phytoplankton, also substitute phospholipids with non-phosphorus forms to decrease cellular demand (Martin et al, 2011; Van Mooy et al, 2009). A transcriptional regulator, distantly related to phosphate starvation regulator protein (PSR1) of Chlamydomonas (Wykoff et al, 1999), was recently found to coordinate such metabolic adaptations in diatoms (Sharma et al, 2019). However, these studies primarily focus on mechanisms underpinning phosphorus limitation responses.…”
Section: Introductionmentioning
confidence: 99%
“…In N. gaditana, 20 putative regulators of lipid production, down-regulated by nitrogen deprivation, were identified by RNA-seq; a strategy of selective knock-out by the Crispr-Cas9 system allowed us to identify a homolog of the fungal Zn(II) 2 Cys 6 -encoding gene, which triggered lipid biosynthesis in Nannochloropsis and resulted in a 200% increase of C partition to lipids, without significantly affecting the growth rate [152]. More recently, a Myb-like transcription factor Phosphorus Starvation Response (PtPSR) was identified in P. tricornutum; its modulation might represent a good strategy to enhance cell growth and TAG production in limited-phosphorous conditions [153]. A MYB DNA binding protein involved in cell cycle regulation was instead targeted in Chlamydomonas, showing that the mutants devoid of CrCDC5 accumulate more oil and starch with respect to WT [154].…”
Section: Engineering Of the Lipid Biosynthesis For Renewable Energiesmentioning
confidence: 99%